2016
DOI: 10.1155/2016/5930589
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TNF-Like Weak Inducer of Apoptosis as a New Marker in Preeclampsia: A Pilot Clinical Study

Abstract: Introduction. All findings of preeclampsia appear as the clinical consequences of diffuse endothelial dysfunction. Soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) was recently introduced as a TNF related cytokine in various inflammatory and noninflammatory disorders. sTWEAK was found to be related to endothelial dysfunction in patients with chronic kidney disease. In our study we aimed to compare sTWEAK levels in women with preeclampsia to corresponding levels in a healthy pregnant contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…This agrees with the standard criteria for diagnosing preeclampsia, as described by the American College of Obstetricians and Gynecologists. Similar to our findings, Yildirim ZK et al [24] discovered that SBP and DBP showed a highly significant elevation in the preeclamptic females than the healthy pregnant females. In addition, Fasshauer M et al [25] found that SBP and DBP were increased in preeclamptic females than healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with the standard criteria for diagnosing preeclampsia, as described by the American College of Obstetricians and Gynecologists. Similar to our findings, Yildirim ZK et al [24] discovered that SBP and DBP showed a highly significant elevation in the preeclamptic females than the healthy pregnant females. In addition, Fasshauer M et al [25] found that SBP and DBP were increased in preeclamptic females than healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…The high-risk group that developed PE/PIH also reported having a significantly lower PLGF value, which strengthened the hypothesis that low sTWEAK is related to the progression of disease severity, indicating the potential of sTWEAK in identifying high-risk cases at the earliest [36]. A similar finding was reported by Yildirim et al 2016, in which sTWEAK levels were significantly lower in pre-eclamptic patients (332 ± 144 pg/mL) than in control subjects (412 ± 166 pg/mL) (p = 0.04). However, the authors warrant further investigation to build evidence on the role of sTWEAK as a predictor for pre-eclampsia [65].…”
Section: Plos Onesupporting
confidence: 76%
“…A similar finding was reported by Yildirim et al 2016, in which sTWEAK levels were significantly lower in pre-eclamptic patients (332 ± 144 pg/mL) than in control subjects (412 ± 166 pg/mL) (p = 0.04). However, the authors warrant further investigation to build evidence on the role of sTWEAK as a predictor for pre-eclampsia [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally 5-14% of all pregnancies are complicated by PE and in developing countries it's prevalence is 4-18% (2). PE is a multifactor disorder, starting with placental dysfunction leading to augmented anti-angiogenic response in mother (3). With the loss of balance between pro-and antiangiogenic factors, the maternal endothelial function deteriorates (4).…”
Section: Introductionmentioning
confidence: 99%
“…sTWEAK is a multipurpose cytokine which is involved in conducting diverse biological events, like cellular multiplication, growth, migration, angiogenesis, cell differentiation, apoptosis and inflammation by instigating expression of multiple pro-inflammatory cytokines. Furthermore, in peculiar it appears to perform critical role in tissue repair and wound healing (3). TWEAK is universally expressed as Type II trans-membrane protein of 35-kDA which after cleaving, shed functionally active soluble 18-kDA processed factor called as sTWEAK (18).…”
Section: Introductionmentioning
confidence: 99%